Comparison between warm blood and crystalloid cardioplegia during open heart surgery - Ferreira, Ricardo (2003)
Objective: This study was designed to compare the degree of myocardial protection afforded by warm blood and cold crystalloid cardioplegia in a group of patients undergoing elective coronary artery bypass surgery. Methods: Seventeen patients, were randomly assigned to Group A (n=9), who received crystalloid cardioplegic solution, and Group B who received warm blood cardioplegic solution (n=8). Before the aorta was clamped, and 10 min after reperfusion, blood samples from the coronary sinus were obtained to assay α-tocopherol, β-carotene, ubiquinol, and thiobarbituric acid reactive substances (TBARS). At the same intervals, biopsies from the left ventricle were obtained to determine ultrastructural alterations. Results: No significant changes were observed between preischemia and reperfusion values for both blood and crystalloid groups concerning α-tocopherol, β-carotene, and ubiquinol, and no differences between groups were detected. Values for TBARS in group A were 3.49±0.3 and 5.27±0.45 μM for presichemia and reperfusion samples, respectively (P<0.01). In group B values were 2.6±0.3 and 3.54±0.3 μM, respectively (P=NS). For electron microscopy studies, semiquantitative analysis showed a significant mitochondrial damage in reperfusion biopsies from group A (grades 0, 3 and 4). In group B, no significant changes were observed in mitochondrial damage between preischemia and repefusion biopsies (except for grade 0). Conclusion: These results indicate that blood cardioplegia affords better protection to the myocyte than crystalloid cardioplegia.